Entrepreneurial orientation, competitive advantage, and SMEs' performance: application of firm growth and personal wealth measures - Kibeshi Kiyabo; Nsubili Isaga (Journal of Innovation and Entrepreneurship, 2020)
SMEs' performance can be measured using various indicators. Guided by the resourcebased view, this study aimed at determining the influence of entrepreneurial orientation on SMEs' performance under the mediation of competitive advantage using firm growth and personal wealth measures. Entrepreneurial orientation was adopted as an intangible resource in form of processes. A survey method with cross-sectional design was used to collect data from 300 owners-managers of welding industry SMEs located in Dar es Salaam, Mbeya, and Morogoro urban centers in Tanzania. By the aid of AMOS software, data analysis comprised of developing measurement and structural models using structural equation modeling technique. Sample data were then bootstrapped using 200 samples to determine the indirect effect of entrepreneurial orientation on SMEs' performance through competitive advantage. Findings from this study inform that competitive advantage mediates the relationship between entrepreneurial orientation and SMEs' performance for both firm growth and personal wealth performance measures. This study has contributed to existing literature by providing evidence on use of personal wealth as measures of SMEs' performance. The findings of the study imply that the resource-based view is suitable in describing not only physical resources but also intangible resources such as entrepreneurial orientation. Future studies may investigate the influence of more constructs such as learning orientation on SMEs' performance under the mediation of competitive advantage using the same firm growth and personal wealth performance measures. Such studies will establish whether the findings of this study are specific to entrepreneurial orientation construct or applicable to other constructs as well.
Keywords: 650; Competitive advantage; Entrepreneurial orientation; Firm growth; Personal wealth; SMEs’ performance